Evaluating Human Immune Responses for Vaccine Development in a Novel Human Spleen Cell-Engrafted NOD-SCID-IL2rγNull Mouse Model - Ghosn, Stéphanie; Chamat, Soulaima; Prieur, Eric; Stephan, Antoine; Druilhe, Pierre; Bouharoun-Tayoun, Hasnaa (Frontiers in Immunology, 2018)
The lack of preclinical models able to faithfully predict the immune responses which are later obtained in the clinic is a major hurdle for vaccines development as it increases markedly the delays and the costs required to perform clinical studies. We developed and evaluated the relevance to human immune responses of a novel humanized mouse model, Hu-SPL-NSG, in which we grafted human spleen cells in immunodeficient NOD-SCID-IL-2rγnull (NSG) mice. We selected the malaria vaccine candidate, LSA3-Full Length (LSA3-FL), because we had previously observed a major discrepancy between pre-clinical and clinical results, and compared its immunogenicity with that of a shorter form of the molecule, LSA3-729. NSG mice engrafted with human spleen lymphocytes were immunized with either LSA3-Full-Length or LSA3-729, both adjuvanted with Montanide ISA 720. We found that the shorter LSA3-729 triggered the production of human antibodies and a protective Thelper-type1 cellular immune response whereas LSA3-Full-Length did not. Results were consistent in 5 groups receiving lymphocytes from 5 distinct human donors. We identified antigenic regions in the full-length molecule, but not in the shorter version, which induced T-regulatory type of cellular responses. These regions had failed to be predicted by previous preclinical experiments in a wide range of animal models, including primates. Results were reproducible using spleen cells from all 5 human donors. The findings in the Hu-SPL-NSG model were similar to the results obtained using LSA3-FL in the clinic, and hence could have been used to predict them. The model does not present graft versus host reaction, low survival of engrafted B lymphocytes and difficulty to raise primary immune responses, all limitations previously reported in humanized immune-compromised mice. Results also point to the shorter construct, LSA3-729 as a more efficient vaccine candidate. In summary, our findings indicate that the Hu-SPL-NSG model could be a relevant and cost-saving choice for early selection of vaccine candidates before clinical development, and deserves being further evaluated.